KNOWLEDGE, ATTITUDE, AND PRACTICE ON MEDICO-LEGAL AUTOPSY AMONG UNDERGRADUATE STUDENTS IN A MEDICAL COLLEGE IN NASHIK, INDIA: A CROSS-SECTIONAL ANALYTICAL STUDY (Journal of Forensic Medicine & Toxicology, 2025)
Background: Forensic medicine integrates various medical disciplines, providing a holistic understanding of human anatomy, Physiology. Medico-legal autopsy is a crucial aspect of forensic medicine that plays a vital role in unraveling the mysteries surrounding suspicious deaths. This paper aims to assess the knowledge, attitude, and practice of medico-legal autopsy among medical students. Method: A cross-sectional questionnaire-based survey was done among the 2nd and 3rd year undergraduate Medical students. Result: A total of 159 (66.3%) participants out of 240 responded during the data collection. It was found that the male students (59.1%) are more in favor of in-depth study of Forensic Medicine than the females (40.9%). Further, statistically significant gender differences in positive responses were seen in issues such as autopsy skill training from 2nd year (M-19.5%, F-(20.1%)), active participation in performing autopsies (M-59.1% F-40.9%) and conducting an autopsy under observation should be a part of the internship (M-48.4%, F-39.6%) among other findings. Conclusion: By integrating medical knowledge with legal and investigative skills, forensic medicine can provide a unique and rewarding career path for those interested in making a difference in both the medical and legal fields.
Keywords: Medico-legal autopsy; Medical Students; Undergraduate; teaching